Technical problems of two garment industries in Clark Air Base - Macapagal, Karen C.; Mayo, Adelaida V. (1999.)
This study entitled "Technical Problems of Two Garment Industries in Clark Air Base" is aimed at finding out the technical problems of the garment manufacturing firms in Clark Air Base. Various literatures were read that helped the researcher in coming up with conceptual framework of the study. Factors considered were technical know-how, raw materials supply, and manpower resources. The study utilized the descriptive-survey method of research with the purpose of finding the technical problems of the two garment industries in Clark Air Base that responded favorably to become subjects of this study, namely; Lintex International Incorporated and Pastel Clothing International Corporation. For the purpose of gathering data, two types of questionnaires were designed: one for the administration and the other for he plant workers. The first dealt with nature of the business organization and its management; the second dealt with the profile of the manpower resources. To support the data gathered from the questionnaire, the interviews and observations were also conducted in the location of the two companies. With regards to sampling procedure, the random sampling method was used to select the plant workers who will participate in the survey. However, the first questionnaire that asked about the nature of the company was assigned purposely to the person or persons cleared by the management to answer the questions. The data gathering lasted for about two months. The researcher also made several follow-up visits to retrieve the questionnaires. The management of the two companies were hesitant to give out many data, thus, the researcher were only able to use limited data for these study, Data gathered were coded, tallied, summarized and presented in tables to facilitate reference analysis. Statistical tools used are measures of central tendency like the mode, median, and mean. Percentages were also used to describe data. Findings of this study were limited to the two companies who agreed to be subjects of this study. They were not conclusive of all the garment firms in the Clark Special Economic Zone and the local garment industry as a whole. The study revealed that the two garment industries in the One encounter technical problems at present. Although these problems may include managerial and financial, the study was limited to the problems in production. Seven major problems related to production that Lintex International Corporation have at present have been identified. These were difficulty in adapting to new designs, inadequate maintenance of machines, off shading of fabrics, wrong cut of garment pieces, improper layout of fabrics, high rejection of finished garments, and improper assortment during packaging. All except one (off shading of fabric), are worker-related. It also showed that 100% of is raw materials were being imported from other countries. This contributed to delay in production and delivery schedules when there was lack of raw materials supply. As to remuneration, workers of the two different companies have a different way of compensating their workers of the two different companies have a different way of compensating their workers. In Lintex International Incorporated, workers were being paid on a piece rate basis while in Pastel Clothing International Corporation, they were being paid on a fixed rate basis. It was found that the standard of labor compensation should be improved to avoid personnel conflicts in the future. Majority of the workers were young and with only highschool background. The work was highly skilled and the production of quality garment depended greatly on the efficient performance of workers. Training and efficiency should be properly attended. It was found out that the working conditions in the company were fair to adequate. The standards of measurement were patterned from Lydia Arribas' instrument used in the special problem he conducted for the University of the Philippines. With these findings, the researcher recommends that a more detailed and extensive study of the garment industry should be undertake to be able to determine a more comprehensive analysis on the existing garment industry in Clark Special Economic Zone. The various standards for measurement should be designed to adapt to the conditions existing in garment-manufacturing firms. The questionnaires as instrument of data gathering should be improved to facilitate the conduct of the survey.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade -- Philippines -- Pampanga